Internationalized criminal courts and tribunals : Sierra Leone, East Timor, Kosovo, and Cambodia, por Cesare P.R. Romano, Andre Nollkaemper and Jann K. Kleffner (eds.), Oxford : Oxford University Press, 2004 - Borgoño, José Luis (Estudios Internacionales, 2005)
-